PENGARUH KUALITAS LAYANAN DAN KEPUASAN PELANGGAN TERHADAP LOYALITAS PELANGGAN PADA APLIKASI GOPAY - Renandia Chandra Putri; Maysharoh, Daril Fajar Ardiyansyah (CV. Adiba Aisha Amira, 2025)
Financial technology (fintech) has influenced people's behavior in financial transactions, including the use of digital wallets such as GoPay. As mobile phone users and internet access increase, the use of GoPay continues to grow. However, competition with other platforms creates a need to understand user behavior, especially related to service quality and customer satisfaction. This study aims to analyze whether service quality and customer satisfaction affect GoPay user loyalty and whether customer satisfaction and service quality have a direct or indirect effect on customer loyalty through customer satisfaction on the GoPay application. This study uses a quantitative method, which is descriptive in nature which aims to describe the data that has been collected and then draw conclusions even though it is not general. The results of this study indicate that the Service Quality variable (X1) has a positive effect on Customer Satisfaction. This is evidenced by the p-value which shows ≤ 0.05 and t- statistic> 1.64 so that it meets the significance criteria. Then the Service Quality variable (X2) which also has a positive effect on User Loyalty as evidenced by the p-value ≤ 0.05 and t- statistic> 1.64, so that the results show a significant relationship. The last is the Customer Satisfaction variable (X3) also has a positive effect on User Loyalty. This is proven by the p- value ≤ 0.05 and t-statistic > 1.64 which meets the significance criteria.